Someone is missing! - Butler, Dori Hillestad (Butler, Dori Hillestad. Dear Beast, 2021)
Through a series of letters, snobby cat Simon and good-natured dog Baxter team up--sort of-- to find Andy's missing school pet Louie, the leopard gecko.